Answer:
The solution for y = -1.
Step-by-step explanation:
Given:
....(1)
....(2)
So, to solve for y, first we solve for x in equation (2):
⇒
Dividing both sides by 2,
⇒
Now, substituting the value of x in equation (1):
⇒
⇒
⇒
⇒
⇒
Dividing both sides by 11,
⇒
Therefore, the solution for y = -1.
When you want to write a polynomial, you should write the term with the highest degree first.
Here, it should go like this: d^3 + d^2 - d + 3
This means that the term which should be written first is the cubic term.
Answer:
x12
Step-by-step explanation:
Answer:
Step-by-step explanation:
what is the question?